ELASTO-PLASTIC STRESS ANALYSIS IN LAMINATED THERMOPLASTIC COMPOSITE PLATES WITH AN ELLIPTIC HOLE - Orçen, Gurbet; Gür, Mustafa (My University, 2013)
In this paper, elasto-plastic stress analysis in laminated thermoplastic composite plates having an elliptic hole in the middle is examined by using finite element method. Composite plates consist of four orthotropic laminations and bonded symmetrically [?0/-?0]. Uniform loadings in vertical direction are applied to the selected composite plates. The loading and reinforcement angle are gradually increased from the yield point of the plate. The load steps increased as 0.0001 MPa at each iteration. Iteration numbers are chosen 25, 50, 75 and 100. A quarter of the plate is taken into consideration due to symmetry. Elasto-plastic stresses are obtained according to load steps and orientation angles.
Keywords: Matematik